A Emergência da agroindústria de processamento de frutas no nordeste paraense, região metropolitana de Belém e no Marajó: uma análise do potencial da capacidade produtiva e inovativa sob a ótica de Arranjo e Sistema Produtivo Inovativo Local – ASPL - ANDRADE, Wanderlino Demetrio Castro de (Universidade Federal do Pará, 2012)
The Local Productive Arrangement (LPA) of Fruits Processing from Northeast of Pará State, Belém Metropolitan Region and Marajó Isle, in Brazilian Oriental Amazon, destines to attend national, regional and local markets. It offers products from exotics and regional fruits. The rural base presents yielding capacity increasing shaped from family farmers. Those farmers have guided their yields to complexity and diversification, where fruits production have highlight in this process. The LPA distinguishes so much informal structures (micro-scale) of açaí processing (local market) well as large scale industries guided exports. The LPA presents high growth rates but with potential of renting limited by structural conditions. One hand those limitations reflecting the short level of governance and cooperation amongst firms. In other hand, are outcome of little interaction capacity amongst enterprises set with the institutional environment. Thus, there are difficulties to consolidate and raise the yielding and innovative capacity of the firms.